1962
DOI: 10.1172/jci104665
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Lactate and Pyruvate Metabolism*

Abstract: Although the heart has been considered primarily an aerobic organ, recent work (1) has reemphasized the possibility that measurement of oxygen consumption alone may not 1)e adequate to define the total energy utilization under all conditions. The role of anaerobic metabolism must be reviewed.Methods of defining as well as quantifying anaerobiosis are currently in dispute. When oxidation and glycolysis proceed at the same rate, carbohydrate is oxidized to CO2 and H20. Lactate arises whenever the rate of glycoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Huckabee and associates suggested that production of lactate in excess of pyruvate, "excess lactate," was a sensitive indicator of myocardial hypoxia (39). Results of animal and clinical research have emphasized that myocardial lactate production alone is a reliable indicator of anaerobic metabolism (65)(66)(67)(68)(69)(70)(71)(72) while lactate extraction less than 10% is suggestive of myocardial hypoxia (65). An increased lactate to pyruvate ratio in the coronary sinus compared to arterial blood is believed indicative of inadequate myocardial metabolism (73)(74)(75).…”
Section: Critique Of Experimental Methodsmentioning
confidence: 99%
“…Huckabee and associates suggested that production of lactate in excess of pyruvate, "excess lactate," was a sensitive indicator of myocardial hypoxia (39). Results of animal and clinical research have emphasized that myocardial lactate production alone is a reliable indicator of anaerobic metabolism (65)(66)(67)(68)(69)(70)(71)(72) while lactate extraction less than 10% is suggestive of myocardial hypoxia (65). An increased lactate to pyruvate ratio in the coronary sinus compared to arterial blood is believed indicative of inadequate myocardial metabolism (73)(74)(75).…”
Section: Critique Of Experimental Methodsmentioning
confidence: 99%
“…Indirect evidence has been provided by animal experiments in which reduction of the coronary blood supply to areas of left ventricle reduced myocardial oxygen consumption, reversed the normal myocardial extraction of lactate from arterial blood, and depressed ventricular function (2)(3)(4). Studies in patients with arteriographically demonstrable coronary lesions have shown increased extraction of oxygen from the coronary circulation (5), increased levels of lactate in coronary venous blood (6), and local abnormalities of ventricular wall contraction during induced angina pectoris (7).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen content was determined from P02, PH, and hemoglobin using a Severinghaus nomogram (20) and assuming a normal hemoglobin-oxygen dissociation curve. Serum lactate was measured by a modification of the enzymatic method of Horn and Bruns (21,22). Myocardial oxygen consumption was calculated as the product of coronary blood flow and arterial-coronary venous oxygen difference ({A-CV}02 difference).…”
Section: Methodsmentioning
confidence: 99%